Association of Placental Growth Factor with the risk of adverse pregnancy outcomes: a prospective cohort study in Chinese pregnant women - Li, Tai-Shun; Wang, Yuan; Wang, Ya; Tang, Hui-Rong; Duan, Hong-Lei; Zhao, Guang-Feng; Li, Jie; Hu, Ya-Li (Frontiers in Endocrinology, 2025)
BackgroundAdverse pregnancy outcomes, such as preterm birth, preeclampsia (PE), small for gestational age (SGA), pose significant risks to maternal and neonatal health and contribute to healthcare burdens. Placental Growth Factor (PIGF), a key pro-angiogenic biomarker involved in placental development, has been implicated in the pathophysiology of these complications. This study aimed to investigate the association between maternal serum PIGF levels and adverse pregnancy outcomes in a prospective cohort.MethodsWe conducted a cohort study involving 5,870 women with singleton pregnancies enrolled at Nanjing Drum Tower Hospital from January 2017 to September 2020. Participants were followed from early pregnancy (≤14 gestational weeks) through delivery. Logistic regression models were used to evaluate the associations between serum PIGF levels (measured at 11–14 gestational weeks) and adverse pregnancy outcomes, reported as adjusted odds ratios (ORs) with 95% confidence intervals (CIs). Dose–response relationships were assessed using restricted cubic spline analysis.ResultsSerum PIGF concentrations in early pregnancy were inversely associated with PE (OR = 0.97, 95% CI:0.96 – 0.98), preterm PE (OR = 0.96, 0.94 – 0.98), SGA <10th percentile (OR = 0.99, 0.98 – 0.99) and SGA <3rd percentile (OR = 0.98, 0.97 – 0.99). Expressed as multiples of the median (MoM), PIGF showed stronger associations with these outcomes, including PE (OR = 0.32, 0.21 – 0.48), preterm PE (OR = 0.23, 0.09 – 0.56), SGA <10th percentile (OR = 0.67, 0.54 – 0.83) and SGA <3rd percentile (OR = 0.43, 0.29 – 0.64), compared with its absolute concentrations. Notably, PIGF demonstrated a consistent inverse association with PE across different modes of conception, including spontaneous pregnancies (OR = 0.97, 0.96 – 0.98) and those conceived via ovulation induction or in vitro fertilization (OR = 0.95, 0.92 – 0.97). The highest predictive performance for PE was observed between 28–34 gestational weeks, with an area under the curve (AUC) of 0.79 (95% CI: 0.77 – 0.81). Additionally, dose–response analysis revealed nonlinear associations between PIGF levels and risks of SGA <10th and SGA <3rd.ConclusionThis cohort study reinforces the inverse association between maternal PIGF levels and the risks of PE and SGA. The findings highlight the potential clinical utility of PIGF as a gestational age–specific biomarker in prenatal risk stratification.